Die Entwicklung der wissenschaftlichen Fragestellung in der Völkerkunde seit Friedrich Ratzel und Adolf Bastian - Trimborn, Hermann (ERDKUNDE, 1959)
Ethnology is one of the few links left between the natural sciences and the humanities, because the subject of ethnology, man, is dealt with both as a biological and as an intellectual being. Therefore it is not appropriate to consider ethnology merely as some sort of historical study, for its many-sided tasks can only be matched by a corresponding manysidedness of methods. This paper reviews the principal methodological trends of the past decades and of the present time. It first deals with 'evolutionalism', which finds a revival in the modern 'neo-evolutionistic' tendencies, and then discusses in detail the development of ideas leading to the concept of the so-called 'Kulturkreis lehre’. Commencing with the suggestions of F. Ratzel the paper discusses the methodological positions of Frobenius, Grabner, W. Schmidt and menghin, and points out the relation between ethnology and prehistory. The particularities of the 'Kulturmorphologie' and the American 'culture areas' are described, and the errors of the historical schools are weighed against their lasting merits. It is also shown which tasks apart from historical research have become of major interest, as for instance the search for 'patterns of culture' (Benedict), the endeavours known by the collective name 'functionalism', and linked with these 'social anthropology'. It is further shown, how the modern issues of the under-developed countries and the world-wide process of acculturation impose new and urgent tasks upon ethnology, and why the growing importance of psychology, especially of analytic and social psychology, for ethnological studies has to be carefully watched. All these perspectives are incompatible only, when superficially looked at; in fact, they are all but a special aspect of the same subject, and they all contribute their various findings towards a fruitful co-operation. Regarding the relation between ethnology and human geography, F. Ratzel had not recognized yet their different points of view: Both have the same subject, but deal with different problems; human geography is concerned with the environment, while ethnology is interested in the ways of life as creations of the human mind.